Finite element analysis for stress distribution of hand tool harvester - M. Abd Halim, Abdul Ssomad; Razali, Mohd Hudzari; Mohd Noor, Noordin Asimi; Salit, Mohd Sapuan; Ngah, Norhayati; Abdullah, Soran Jalal (Elsevier, 2013)
This paper introduced the essential development of an innovative hand tool harvester since harvesting the tuber of Dioscorea hispida is tedious and difficult while the existing hand tool is heavy. The information of optimum force required from field experiment is used to model the simulation and practicability in Computer Aided Design (CAD) environment system. Several tests of maximum/minimum stress and displacement on different material of hand tool were simulated by uploading the material characteristic on simulation program embedded in Solidworks software. Three materials which were commonly available in market namely Plain Carbon Steel, Aluminium Alloy and Cast Carbon Steel were chosen. This modeling software is very helpful to manage the model and simulate the workability of the designed equipment through stress and displacement mode analysis. The comparison between the tools that are based on the acquired land and tuber weight factor were also noted via Solidworks simulation. The end result of the simulation is based on visualization of analysis in Solidworks while producing the hand tool for designing and fabrication from lighter and stronger material.